A NUTRITION STUDENT IN NATIONAL FOOD AND NUTRITIONAL SECURITY - Bruna dos Santos Nunes (Universidade do Estado do Rio de Janeiro, 2013)
LETTER TO THE EDITOR Dear Editors of Journal DEMETRA: Alimentação, Nutrição & Saúde / Food, Nutrition & Health magazine: I am addressing the editors of journal DEMETRA to request the publication of my report about my experience during the curricular internship at the Nutrition course at the University of Brasilia. I chose this journal as suggested by my internship supervisor, Elisabetta Recine, Professor in the  Department of Nutrition at the University of Brasilia.